55‐1: Deposition of Conductive and Insulating Materials at Micrometer Scale for Display‐Component Prototyping. Issue 1 (28th June 2022) - Łysien, Mateusz; Witczak, Łukasz; Gadzalińska, Jolanta; Grądzka-Kurzaj, Iwona; Schneider, Ludovic; Wiatrowska, Aneta; Fiączyk, Karolina; Kowalczewski, Piotr; Granek, Filip
Abstract : Ultra‐Precise Deposition (UPD) is an additive manufacturing process for fabricating conductive and non‐conductive features at micrometer scale. The method is compatible with a wide range of materials, which makes it particularly suitable for rapid prototyping of high‐resolution displays and its components. In this contribution we will discuss the means to control the process and give a number of examples that can be considered as building blocks for display‐component prototyping, making the process more productive and cost‐efficient. We consider materials based on silver, copper, and gold, as well as photoresists.